Contribution to the knowledge of Bonamia (Convolvulaceae) in Brazil: a new species and a new occurrence - Moreira, André Luiz Da Costa; Antar, Guilherme Medeiros; Simão-Bianchini, Rosângela; Cavalcanti, Taciana Barbosa (Phytotaxa, 2017)
A new species, Bonamia campestris A.Moreira & Sim.-Bianch., from the Jalapão region in the state of Tocantins, Brazil, is described and illustrated. It is compared with morphologically similar species. Additional collections of the recently described Bonamia rosiewiseae J.R.I.Wood extend its range from two locations in eastern Bolivia to Mato Grosso do Sul in southwest Brazil.